2022
DOI: 10.3389/fimmu.2022.929946
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplantation seroreactivity in kidney donors and recipients as a predictive factor for posttransplant BKPyV-DNAemia

Abstract: BK polyomavirus (BKPyV) often reactivates after kidney transplantation, causing BKPyV-associated nephropathy (BKPyVAN) in 1%–10% of cases with a potential detrimental effect on allograft survival. Kidney transplant recipients are regularly screened for BKPyV DNA in plasma. As this strategy may not always reduce the risk of BKPyVAN, other predictive markers are needed. To evaluate the role of pretransplant BKPyV-specific antibody, 210 kidney transplant recipients and 130 donors were screened for BKPyV DNA and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…These findings are consistent with the those of Saláková et al. ( 16 ) who established a significant correlation between donor seropositivity and recipient post-transplant BKV infection. A trend toward donor seropositivity and BKVAN was observed in their study, but lacked statistical significance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with the those of Saláková et al. ( 16 ) who established a significant correlation between donor seropositivity and recipient post-transplant BKV infection. A trend toward donor seropositivity and BKVAN was observed in their study, but lacked statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, Saláková et al. reported that the donor BKV-IgG seroprevalence and antibody level were strongly associated with posttransplant BK viremia and BKVAN in a study of 210 KTRs and 130 donors ( 16 ). Finally, they confirmed recommendation by Hirsh and Randhawa that KTRs from seropositive donors should be routinely screened for BKV-DNA in plasma much more frequently than KTRs from seronegative donors ( 5 ).…”
Section: Introductionmentioning
confidence: 99%